Volume 6: Turbomachinery, Parts A, B, and C 2008
DOI: 10.1115/gt2008-50214
|View full text |Cite
|
Sign up to set email alerts
|

Active Flow Control in a Single-Stage Axial Compressor Using Tip Injection and Endwall Boundary Layer Removal

Abstract: Different active flow control techniques have been investigated in a 1.5-stage axial-flow compressor. Looking at a low-speed single-stage environment, many researchers have shown that highly loaded compressors are tip critical, showing stall inception caused by short length scale disturbances (spikes). It has been shown by several authors that these disturbances are related to the spillage of endwall flow ahead of the blading (spill forward). For the present work, different tip injection configurations were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…It has been also found that casing aspiration can effectively improve the performance and stability by controlling of TLF and the associated loss generation in compressor stages. [56][57][58] In addition, Tuo et al 67 showed that the unsteady excitation frequency due to the slot number of casing treatment is one of the most important factors influencing the compressor performance. Therefore, the unsteady effects between the aspiration slots and rotor are likely to exist when applying casing aspiration in rotor blade rows and the number of aspiration slots should be considered in detail in the process of casing aspiration design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been also found that casing aspiration can effectively improve the performance and stability by controlling of TLF and the associated loss generation in compressor stages. [56][57][58] In addition, Tuo et al 67 showed that the unsteady excitation frequency due to the slot number of casing treatment is one of the most important factors influencing the compressor performance. Therefore, the unsteady effects between the aspiration slots and rotor are likely to exist when applying casing aspiration in rotor blade rows and the number of aspiration slots should be considered in detail in the process of casing aspiration design.…”
Section: Discussionmentioning
confidence: 99%
“…[52][53][54][55] There are several investigations of aspiration techniques on the control of TLF to improve the compressor performance and stability. 51,[56][57][58] Additionally, very little study has been conducted on the effectiveness of different aspiration locations on the casing and the control mechanisms of the different aspiration schemes.…”
Section: Introductionmentioning
confidence: 99%
“…In order to avoid the use of guide vanes and thereby to increase the efficiency of the fan rotation direction of impellers they are made opposite [9,10].…”
Section: Resultsmentioning
confidence: 99%
“…So far the studies about suction mainly concentrate on the control of the boundary layer separation on the blade SS (Song et al 2006;Guo et al 2010;Shi et al 2015b) or the three-dimensional (3D) separation in the hub corner (Sachdeva et al 2011;Pönick et al 2013;Guo et al 2008;Marsan et al 2015). Apart from some researches about the effects of bleeding system on the compressor performance (Leishman et al 2007a(Leishman et al , 2007b(Leishman et al , 2007cGrimshaw et al 2015Grimshaw et al , 2016, there are only several investigations of suction technique on the control of TLF to improve the compressor performance and stability (Gümmer et al 2008;Dobrzynski et al 2008;Shi et al 2015a). It is found that the flow fields in the tip region and operating range can be improved by the suction on the casing.…”
Section: Introductionmentioning
confidence: 99%